2020
DOI: 10.1007/s10570-020-03263-x
|View full text |Cite
|
Sign up to set email alerts
|

On the strength improvement of lightweight fibre networks by polymers, fibrils and fines

Abstract: Novel lightweight cellulose fibre materials containing various strength enhancing polymeric and fibrillar components were formed with the help of foam technology. Increasing inter-fibre bond strength and local material density was attempted with unique lignin-containing wood fines (V-fines), cellulose microfibrils (CMF), TEMPO-oxidized cellulose nanofibrils (TCNF), and macromolecules such as cationic starch, polyvinyl alcohol (PVA), and locust bean gum (LBG). The investigated fibres included both long hemp bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…fibres that are more aligned to the direction of gravity. Increasing the initial liquid fraction of the foam increases the fraction of support fibres; it also has the effect of increasing the compressive modulus of the fibrous material, which could be further increased by the addition of polymers or fibrils [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…fibres that are more aligned to the direction of gravity. Increasing the initial liquid fraction of the foam increases the fraction of support fibres; it also has the effect of increasing the compressive modulus of the fibrous material, which could be further increased by the addition of polymers or fibrils [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in the recent work by [ 7 ] neither the wet foam fibre dispersions nor the dried sample are compressed. This results in samples of density 13 kg.m -3 compared with densities of about 40 kg.m -3 by [ 7 ].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is possible that the interaction is stronger for the hardwood fibers because of their chemical heterogeneity (amphiphilicity) and trapped air (nanobubbles) on rough fiber surfaces. [31,77] On the other hand, the addition of 2.5% of MFC increases the consistency index by 25%. The small size of MFC fibers limits their ability to distribute momentum, while hardwood fibers can interact simultaneously with tens or even hundreds of bubbles.…”
Section: Bulk Rheology Of Foammentioning
confidence: 99%
“…Despite this rather drastic change in the fiber foam structure, traces of bubble structure still remain visible in the final dried sheet. [21,77,129,130] Al-Qararah [22] showed that lower density can be achieved in a sheet sample by using foam as the carrier phase instead of water with equal surfactant concentration. Thus, the bubble structure is essential in setting the densitynot only the reduced bonding because of surfactant.…”
Section: Materials Densitymentioning
confidence: 99%